Blaubeuren, Cloppenburg, and Machtenstein—Three recently recognized H‐group chondrite finds in Germany with distinct terrestrial ages and weathering effects. (17th January 2022) - Bischoff, Addi; Storz, Jakob; Barrat, Jean‐Alix; Heinlein, Dieter; Jull, A. J. Timothy; Merchel, Silke; Pack, Andreas; Rugel, Georg
Abstract: In the last 7 years, three meteorites (Blaubeuren, Cloppenburg, and Machtenstein) found in Germany were identified as chondrites. Two of these rocks had been recovered from the impact sites decades ago but were not considered to be meteorites. The aim of this study is to fully characterize these three meteorites. Based on the compositional data on the silicates, namely olivine and low‐Ca pyroxene, these meteorites fit nicely within the H‐group ordinary chondrites. The brecciated texture of Blaubeuren and Cloppenburg (both H4‐5) is perfectly visible, whereas that of Machtenstein, officially classified as an H5 chondrite, is less obvious but was detected and described in this study. Considering chondrites in general, brecciated rocks are very common rather than an exception. The bulk rock degree of shock is S2 for Blaubeuren and Machtenstein and S3 for Cloppenburg. All samples show significant features of weathering. They have lost their original fusion crust and more than half (W3) or about half (W2‐3) of their original metal abundances. The oxygen isotope compositions of the three chondrites are consistent with those of other H chondrites; however, the Cloppenburg values are heavily disturbed and influenced by terrestrial weathering. This is supported by the occurrence of the very rare hydrated iron phosphate mineral vivianite (Fe 2+ Fe 2+ 2 [PO4 ]2 ·8H2 O), which indicates that the chondrite was weathered in a very wet environment. The terrestrial ages of Blaubeuren (~9.2 ka), Cloppenburg (~5.4 ka), and Machtenstein (~1.8 ka) show that these chondrites are very similar in their degree of alteration and terrestrial age compared to meteorite finds from relatively wet terrestrial environments. They still contain abundant metal, although, as noted, the oxygen isotope data indicate substantial weathering of Cloppenburg. The bulk compositions of the three meteorites are typical for H chondrites, although terrestrial alteration has slightly modified the concentrations, leading in general to a loss of Fe, Co, and Ni due to preferential alteration of metals and sulfides. As exceptions, Co and Ni concentrations in Machtenstein, which has the shortest terrestrial age, are typical for H chondrites. The chemical data show no enrichments in Ba and Sr, as is often observed in different meteorite groups of desert finds.